Microplastics in Asian rivers: Geographical distribution, most detected types, and inconsistency in methodologies - Hsin, Tien Lin; Schneider, Falk; Aziz, Muhamad Afiq; Keng, Yinn Wong; Arunachalam, Kantha D.; Praveena, Sarva Mangala; Sethupathi, Sumathi; Woon, Chan Chong; Nafisyah, Ayu Lana; Parthasarathy, Purushothaman; Chelliapan, Shreeshivadasan; Kunz, Alexander (Elsevier, 2024)
Microplastics pose a significant environmental threat, with potential implications for toxic chemical release, aquatic life endangerment, and human food chain contamination. In Asia, rapid economic growth coupled with inadequate waste management has escalated plastic pollution in rivers, positioning them as focal points for environmental concern. Despite Asia's rivers being considered the most polluted with plastics globally, scholarly attention to microplastics in the region's freshwater environments is a recent development. This study undertakes a systematic review of 228 scholarly articles to map microplastic hotspots in Asian freshwater systems and synthesize current research trends within the continent. Findings reveal a concentration of research in China and Japan, primarily investigating riverine and surface waters through net-based sampling methods. Polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET) emerge as the predominant microplastic types, frequently observed as fibers or fragments. However, the diversity of sampling methodologies and reporting metrics complicates data synthesis, underscoring the need for standardized analytical frameworks to facilitate comparative analysis. This paper delineates the distribution of microplastic hotspots and outlines the prevailing challenges and prospects in microplastic research within Asian freshwater contexts.